Optimal Land Use for Rainfall-Runoff Transformation in Wae Ruhu Watershed - Laturua, Aly; Hendrayanto, .; Puspaningsih, Nining (Media Konservasi, 2018)
Flooding hit the island of Ambon in 2012 and 2013. Many analyzes has been developed to estimate the cause of the flooding. The study aims topredict optimal land management for reducing run-off. The method is simulation of CN value based on spatial analysis on watershed characteristics.The rainfall can’t be managed by watershed. The level of run-off can be determined by CN value that depends on the type of land cover. The resultshows that the land cover has changed about 90 ha, with the higher rainfall intensity is 2.118 in 2013. The result of simulation indicated that tochange of shrub and bare land, mix dryland forest, and secondary dryland forest with agroforestry. Agroforestry can decrease run-off amount 0,86%.The change of land cover and high rainfall are the main factors that caused the flooding in 2012 and 2013. It is necessary to add a rainfallobservation station so that the observation of surface flow can be done well.Keywords: curve number, land cover change, watershed